On the Effect of the Temperature-Humidity Index on Buffalo Bulk Milk Composition and Coagulation Traits - Costa, Angela; De Marchi, Massimo; Battisti, Sabrina; Guarducci, Marcella; Amatiste, Simonetta; Bitonti, Giuseppe; Borghese, Antonio; Boselli, Carlo (Frontiers in Veterinary Science, 2020)
Little is known on the effect of high levels of environmental temperature and humidity on milk yield and quality in buffaloes, since this specie is known to be more heat tolerant than cattle. However, both distribution of sweat glands and the dark skin colour can negatively affect their heat tolerance. Moreover, due to the increased global temperature, concerns regarding heat stress and thermoregulation of dairy animals, including buffaloes, has been extended to the northern hemisphere. In this study, the effect of both the temperature-humidity index (THI) and the maximum daily temperature-humidity index (MTHI) was estimated on bulk milk traits, namely fat, protein, lactose, and urea content, pH, somatic cell score, coagulation properties, and bacteria count. The dataset consisted of repeated data from 99 Mediterranean water buffalo farms and mixed models were used for the analyses. Supporting the negative correlations observed, milk fat, protein and lactose content were significantly lower when THI and MTHI were higher. Milk pH was lower when THI and MTHI were high, however, high levels of THI or MTHI seemed to be not markedly associated to the milk coagulation ability. Confirming the correlations, somatic cell score was not significantly affected by THI and MTHI. This is the first study based on a large dataset that evaluates the impact of high temperature and humidity in Italian buffalo milk and that provides correlations with traits of interest for the dairy industry, i.e. acidity and coagulation traits. In general, findings showed that the effect of elevated THI and heat stress on bulk milk quality in buffalo is less evident than in cattle. Finally, these preliminary results are intended to open the debate on the issue of heat stress in dairy buffaloes reared in the temperate region. Further studies should focus on individual milk and performance and may investigate the relation between high THI and buffalo reproductive performance, behaviour and welfare.